The Role of the Chicago School of Economics in the Genesis of a New Field of Research: “The Economic Analysis of Law” - Ciobanu, Ramona (Transilvania University Press, 2013)
The interdisciplinary approach adopted nowadays, in terms of law and economics, is closely linked to the Chicago School of Economics. This has made a great contribution to the development of economic science and to lawyers it has a special significance because within it the Law and Economics school of thought or Economic Analysis of Law was created. The economic analysis of law uses terms, concepts and economic institutions that apply to different areas of law and it is meant to improve the legal norm.
Keywords: economics; law; the economic analysis of law